2018
DOI: 10.2298/abs170512024d
|View full text |Cite
|
Sign up to set email alerts
|

Environmental drivers of raccoon (Procyon lotor L.) occurrences in Austria - established versus newly invaded regions

Abstract: As we are faced with the imminent spread of the raccoon (Procyon lotor L.), a successful and highly adaptable invader in Europe, it is necessary to identify the drivers of its distribution and focal areas of its future management. Being an omnivorous species, raccoons can exert considerable influence on prey species of various taxa. Species distribution models for this invasive species can be useful tools for its management. Using a presence-only model (MaxEnt) based on environmental variables selected by racc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…The predictions successfully identified the worldwide occurrence records of the raccoon, including native (i.e. North America) and invaded regions (Europe), used in this study and demonstrated high probability values of areas predicted by previous studies such as Italy, Austria and Germany (Fischer et al 2015, Mori et al 2015, Farashi & Naderi 2017, Duscher et al 2018). In addition, our realised distribution model illuminated the current distribution of this species, which is in line with the previous research carried out by Farashi et.…”
Section: Discussionsupporting
confidence: 66%
“…The predictions successfully identified the worldwide occurrence records of the raccoon, including native (i.e. North America) and invaded regions (Europe), used in this study and demonstrated high probability values of areas predicted by previous studies such as Italy, Austria and Germany (Fischer et al 2015, Mori et al 2015, Farashi & Naderi 2017, Duscher et al 2018). In addition, our realised distribution model illuminated the current distribution of this species, which is in line with the previous research carried out by Farashi et.…”
Section: Discussionsupporting
confidence: 66%
“…As a next step, models should incorporate land‐use variables on a European scale in order to further differentiate and localise suitable and potentially overlapping habitats for both species (for land‐use models applied to Procyon lotor; see Fischer et al 2016, Germany; Duscher et al 2018, Austria). Variables related to the influence of humans, such as population density or urbanisation, might also be considered (Srivastava et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As their diets and habitat use are very plastic, the only factor that might be limiting both species is climate. Climatically favourable areas have been predicted on a regional scale in Italy (Mori et al 2015) and on a global scale (Louppe et al 2019) for Procyon lotor , as well as for both species in Austria (Duscher & Nopp‐Mayr 2017, Duscher et al 2018), using various modelling approaches. We compare the native‐range niches of both species in North America and East Asia with their non‐native‐range niches in Europe, based on eight bioclimatic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Dijak and Thompson 2000;Chamberlain et al 2007) and introduced range (e.g. Farashi and Naderi 2017;Duscher et al 2018;Fiderer et al 2019). However, neither the size of the water source nor the distance from it affected the occupancy of the raccoon in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…The Northern raccoon (Procyon lotor) is a species included in the Union list because of its invasiveness and the threat it represents to native species and human activities and health. The raccoon is an opportunistic mesocarnivore native to North and Central America that, despite its preference for riparian forests (Heske and Ahlers 2016;Duscher et al 2018;Fiderer et al 2019), can adapt to new environments exploiting a wide variety of habitat and food resources (Prange et al 2004). Raccoons are omnivorous and eat a wide range of plants (seeds, nuts, fruits) and animals like insects, small mammals, amphibians, crabs, fish and birds or bird eggs (Zeveloff 2002; Bartoszewicz et al 2008;García et al 2012).…”
Section: Introductionmentioning
confidence: 99%